Decolonial design practices: Creating safe spaces for plural voices on contested pasts, presents, and futures - Kambunga, Asnath Paula; Smith, Rachel Charlotte; Winschiers-Theophilus, Heike; Otto, Ton (Design studies, 2023)
This article introduces the concept of the ‘safe space’ in design interventions: a socially developed environment for thoughts, actions, and mutual learning in political and contested contexts. The safe space responds to current challenges within decolonial design practices and calls for a plurality of knowledge and voices. We present a study in which we developed safe spaces with young Namibians by combining core elements of design anthropology and community-based participatory design through interventions, dialogic engagements, and co-design. We demonstrate how the intentional design practice of a safe space enables new ways of working in a contested context. The article presents a framework for designing and developing safe spaces, focusing on working with multiple temporalities and the social production of spaces. •A decolonial design approach responding to challenges of decolonial design practices.•The concept of safe space provides a new way of working in a contested context.•Extending the temporal horizons of design by actively engaging with pasts that may suggest alternative futures.•The combination of core elements of design anthropology and participatory design.